2004
DOI: 10.1007/s10350-003-0110-x
|View full text |Cite
|
Sign up to set email alerts
|

Manometric Study of Topical Sildenafil (Viagra®) in Patients With Chronic Anal Fissure: Sildenafil Reduces Anal Resting Tone

Abstract: Topical administration of a phosphodiesterase-5 inhibitor (sildenafil, Viagra) significantly reduces anal sphincter pressure in patients with chronic anal fissure. A beneficial effect of nitric oxide on the spastic anal sphincter has been demonstrated previously. This study confirms that this effect need not be derived solely from nitric oxide donors. New therapeutic avenues for treatment of anal fissure through indirect enhancement of nitric oxide activity are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 36 publications
(38 reference statements)
1
22
0
Order By: Relevance
“…There are some trials focusing on new areas of use sildenafil, including chronic anal fissure [16,17], primary pulmonary hypertension [18], the increasing of retinal blood flow [19], and hypercontractile eosophageal motility disorders [20]. Eherer et al [21] reported that sildenafil reduced basal pressure and sphincter volume of the lower oesophageal sphincter.…”
Section: Discussionmentioning
confidence: 98%
“…There are some trials focusing on new areas of use sildenafil, including chronic anal fissure [16,17], primary pulmonary hypertension [18], the increasing of retinal blood flow [19], and hypercontractile eosophageal motility disorders [20]. Eherer et al [21] reported that sildenafil reduced basal pressure and sphincter volume of the lower oesophageal sphincter.…”
Section: Discussionmentioning
confidence: 98%
“…More recently, Torrabadella et al 24 showed that topical application of sildenafil decreases anal sphincter pressure in patients with chronic anal fissure. Our in vitro study supports this clinical investigation and helps to explain the mechanisms of relaxing action of sildenafil citrate on IAS.…”
Section: Discussionmentioning
confidence: 98%
“…Healing rates of fissura ani has been reported to be >90 percent after lateral internal sphincterotomy. 24 However, several complications, including risk of incontinence, itching, and soilage, may occur after surgical division of the IAS.…”
Section: Discussionmentioning
confidence: 99%
“…Some work has been conducted into their use in the treatment of anal fissures. Torrabadella et al studied the effect of topical application of 10% sildenafil (a phosphodiesterase-5 inhibitor) on the anal sphincter tone of patients suffering from chronic anal fissures [175]. Anal tone was reduced by an average of 18% in less than 3 minutes.…”
Section: Phosphodiesterase-5 Inhibitorsmentioning
confidence: 99%